Intermittent fasting increases adult hippocampal neurogenesis - Baik, Sang‐Ha (Brain Behav, 2019)
INTRODUCTION: Intermittent fasting (IF) has been suggested to have neuroprotective effects through the activation of multiple signaling pathways. Rodents fasted intermittently exhibit enhanced hippocampal neurogenesis and long‐term potentiation (LTP) at hippocampal synapses compared with sedentary animals fed an ad libitum (AL) diet. However, the underlying mechanisms have not been studied. In this study, we evaluated the mechanistic gap in understanding IF‐induced neurogenesis. METHODS: We evaluated the impact of 3 months of IF (12, 16, and 24 hr of food deprivation on a daily basis) on hippocampal neurogenesis in C57BL/6NTac mice using immunoblot analysis. RESULTS: Three‐month IF significantly increased activation of the Notch signaling pathway (Notch 1, NICD1, and HES5), neurotrophic factor BDNF, and downstream cellular transcription factor, cAMP response element‐binding protein (p‐CREB). The expression of postsynaptic marker, PSD95, and neuronal stem cell marker, Nestin, was also increased in the hippocampus in response to 3‐month IF. CONCLUSIONS: These findings suggest that IF may increase hippocampal neurogenesis involving the Notch 1 pathway.